2008
DOI: 10.1002/dneu.20689
|View full text |Cite
|
Sign up to set email alerts
|

ATP and NO dually control migration of microglia to nerve lesions

Abstract: Microglia migrate rapidly to lesions in the central nervous system (CNS), presumably in response to chemoattractants including ATP released directly or indirectly by the injury. Previous work on the leech has shown that nitric oxide (NO), generated at the lesion, is both a stop signal for microglia at the lesion and crucial for their directed migration from hundreds of micrometers away within the nerve cord, perhaps mediated by a soluble guanylate cyclase (sGC). In this study, application of 100 lM ATP caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 51 publications
5
67
0
Order By: Relevance
“…NO's action on the migratory behavior of leech microglia may be mediated by cGMP (228). The leech microglia also has sensitivity to ATP and its analogs, which induce migratory movement; effects of purines were antagonized by reactive blue 2, suggesting the role for P2 purinoceptors (229).…”
Section: Evolutionary Origins Of Microgliamentioning
confidence: 99%
“…NO's action on the migratory behavior of leech microglia may be mediated by cGMP (228). The leech microglia also has sensitivity to ATP and its analogs, which induce migratory movement; effects of purines were antagonized by reactive blue 2, suggesting the role for P2 purinoceptors (229).…”
Section: Evolutionary Origins Of Microgliamentioning
confidence: 99%
“…Using a similar acute brain slice preparation in rats, Kurpius et al [31] also demonstrated that following tissue slicing, which inevitably induces neuronal injury, microglia cells are able to “home” rapidly to neuron-rich regions presumably by sensing endogenously released neuronal purinergic signals. Subsequently, ATP-induced microglial chemokinesis has been confirmed in the mouse spinal cord [19, 32] and retina [21] as well as in other animal models including the zebrafish [33] and leech [34] indicating the widespread existence of this signaling mechanism. The specific receptors involved in purine-induced chemotaxis have also been identified.…”
Section: The Neuron-to-microglia Communication Axismentioning
confidence: 99%
“…These observations suggested that increases in NO level may incur potentially tumor promoting side effects under certain conditions in the neoplastic cells. These and related studies demonstrated a role for NO as a positive regulator of cellular migration and proliferation in both normal and neoplastic cells (Duan et al, 2009; Lu et al, 2015; Yongsanguanchai et al, 2015). …”
Section: Introductionmentioning
confidence: 89%